Statistical and analytical analysis of a data series - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2019)
In a concrete year, at the begining of the month, a company changed the unit price of the notebooks. The company wrote down the demand and the supply. We analyse the data series which the company described.